New remains from the Spanish Cenomanian shed light on the Gondwanan origin of European Early Cretaceous titanosaurs. (March 2019) - Mocho, P.; Pérez-García, A.; Martín Jiménez, M.; Ortega, F.
Abstract: Algora is a recently discovered vertebrate fossil site located in the Cenomanian strata of the Arenas de Utrillas Formation (Guadalajara, Central Spain). This fossil site is rich in turtle remains, but other clades of reptiles are also identified, including plesiosaurs, crocodyliforms and dinosaurs. The only remains of dinosaurs from Algora so far studied corresponded to theropod teeth. However, several sauropod remains are here presented and analyzed, revealing the presence of several shared features with members of Titanosauriformes, some common found in derived members belonging to Lithostrotia clade. This sauropod fossil assemblage corresponds to the richest sauropod fossil accumulation found in the Cenomanian of Europe. In addition, one of the first studies of the pneumatic features in dorsal ribs using CT scan is also provided here. The performed cladistic analysis places the Algora sauropod within Lithostrotia, in a more derived position than Malawisaurus (supported, for example, by the presence of convex posterior articulation up to the posterior section of the tail), in a clade which also includes Rapetosaurus (Maastrichtian, Madagascar) and the Italian indeterminate titanosaur MSNM V7157 (late Aptian–early Albian). The Algora titanosaur and MSNM V7157 are recognized as closely related. This analysis shows the presence of two different lineages (Algora titanosaur + MSNM V7157 and Normanniasaurus, from the Albian of France) in the Early and middle Cretaceous of Europe, and at least one with a Gondwanan origin. The close relationship of the Algora titanosaur and MSNM V7157 suggests a pre-late Aptian faunal contact between the Adriatic Plate and Laurasia, in accordance with several previous studies, which proposed faunal exchanges between Laurasia and Gondwana through the Adriatic plate during the Early Cretaceous.